2018
DOI: 10.1080/13621718.2018.1432098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotation speed on microstructure and mechanical properties of bobbin tool friction stir welded AZ61 magnesium alloy

Abstract: The 5-mm-thick AZ61 magnesium alloy was friction stir welded by using the specially designed bobbin tool with various rotation speeds. Defect-free welds were successfully obtained with rotation speed ranging from 550 to 600 rev min −1 . Grain size in different regions of the joints varied depending on the rotation speed. The hardness value of the joint is uniform. The defective joint fractured in the weld nugget zone with the lowest tensile strength, while the fracture location of the defect-free joints change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…At the initial stage in NZ, the grains bend and get elongated. Further, the highly elongated grains break due to increase in the strain, and this process continues until equiaxed grain is formed [36]. The refinement of grain in TMAZ is mainly influenced by the shoulder friction during FSW where the elongated and tilted grain is formed from top to bottom of AS and RS in TMAZ which is elliptical in shape (as shown in Fig.…”
Section: Microstructural Observationmentioning
confidence: 98%
“…At the initial stage in NZ, the grains bend and get elongated. Further, the highly elongated grains break due to increase in the strain, and this process continues until equiaxed grain is formed [36]. The refinement of grain in TMAZ is mainly influenced by the shoulder friction during FSW where the elongated and tilted grain is formed from top to bottom of AS and RS in TMAZ which is elliptical in shape (as shown in Fig.…”
Section: Microstructural Observationmentioning
confidence: 98%
“…The requirement for groove, complex treatment prior to welding and residual stress and deformation of post-weld structure involved in the conventional welding method could also be limited. However, the presence of significant plunging force and rigid backing plate/anvil to react process loads makes it difficult for some complex-shaped structures to implement the friction stir welding process [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As investigated by Esmaily et al [7], an improved corrosion resistance in BT-FSWed joints was achieved as compared to FSWed joints. For lightweight manufacturing, Zhou et al [8] carried out the BT-FSW of AZ61 magnesium alloy and reported the correlation between mechanical properties and rotational speeds. At the same time, they found a typical region, namely band pattern, where the voids form easily.…”
Section: Introductionmentioning
confidence: 99%